MODEL TADZKIRAH DALAM MENUMBUHKAN DAN MENGEMBANGKAN NILAI NILAI KARAKTER ANAK USIA DINI - Ridwan, Ridwan (Efektor, 2017)
The purpose of this study was to develop a tadzkirah model in growing and developing the values ​​of character. Basically the values ​​of the characters is very difficult to be developed in the absence of appropriate learning strategies. An educator in early childhood education must have knowledge and skills in developing learning models appropriate to the level and condition of the students. This study uses the development of Borg and Gall and the quantitative and quantitative approaches. The model will be validated by three experts that expert learning model, a Science and instructional design experts. The research was conducted in early childhood education institutions Tabroni Kediri. The results of this study states that the model Tadzkirah Very suitably carried by a teacher because it can develop character values ​​early childhood. Tadzkirah model is show exemplary, give guidance, give encouragement or motivation, followed by intent clean (educating), with the process of habituation always reminded, repeated over and done reflection, organizing the knowledge and experience of students and full of tenderness (affection) ,